Platelet Membrane Glycoprofiling in a PMM2-CDG Patient - Papazoglu, Gabriela Magali (2021)
Congenital disorders of glycosylation (CDG) are metabolic hereditary diseases caused by defects in the synthesis of glycoconjugates. CDG have been described in sugar-nucleotide biosynthesis and transporter, glycosyltransferases, vesicular transport, as well as in lipid biosynthesis and glycosylphosphatidylinositol anchors. PMM2-CDG is caused by mutations in the phosphomannomutase-2 (PMM2) gene and shows autosomal recessive inheritance. It affects all organs and tissues, ranging from severe psychomotor retardation to moderate intellectual disability. Alterations in the primary haemostatic system have been reported in these patients and they can lead to severe bleeding or excessive thrombosis with subsequent vascular insufficiency. Despite of being the most common CDG, platelet glycosylation and sialylation defects in PMM2-CDG patients remain incompletely characterized. In this study, we applied a lectin-based flow cytometry approach to report the first characterization of the highly glycosylated platelet membrane glycan profile in a PMM2-CDG patient. In the PMM2-CDG patient’s platelet samples, a decreased binding of SNA lectin, indicative of reduced terminal α-2-6 sialic acid content, and an increased binding of PNA lectin, suggesting desialylation of β-1-Nacetylgalactosamine residues, were observed. Reduced expression of terminal sialic acids in platelet membrane glycoproteins may contribute to the increased risk of hemorrhage reported in these patients by promoting platelet clearance and thrombocytopenia.